Design of Micro Hydro Power Plant System Prototype with Arduino Uno-Based Dummy Load - Geri Geraldo Salam; Ahmad Raditya Cahya Baswara (Universitas Ahmad Dahlan, 2023)
Electricity is a vital need and economic resource that is needed for all communities. One of the electricity technologies that can be generated from water is utilizing water discharge to be converted into electrical energy or called PLTMH (Microhydro Power Plant). This research has been done but still needs to be developed, for example on an automatic loading system. With the help of a 1 channel relay to control the dummy load automatically. This research uses 2 different test simulations and different wiring circuits. The results of this study show that in simulation 2 the dummy load system cannot run at all. Due to the voltage value read is not so stable by the ZMPT101B sensor. The spike of the read voltage value causes it to be difficult for the relay to analyze the voltage value then causes the logic on the relay to be disturbed and an error occurs in the automatic dummy load system. However, in simulation 1 the dummy load system can work properly. For comparison of voltage values between a multimeter with a voltage value of 4.5 V (before adding a load) and on the Arduino IDE with an average of 4.564 V, the average error is -1.42222. For comparison of frequency values between multimeter 47 Hz without load and on Arduino IDE with an average value of 47 Hz with an average error of -0.8, from ac generator rotation with a voltage value of 4.5V.